Practicioner Profile: An Interview with Ted Klontz, Ph.D. (Journal of Financial Therapy, 2010)
Dr. Ted Klontz is generally considered to be one the leading pioneers in the field of financial therapy. He defines his role as a consultant, but this simple term masks the important role he has played in changing the attitudes and behaviors of clients worldwide. His innovative work has been cited in the Wall Street Journal, the New York Times, and ABC’s 20/20 to name a few. Dr. Klontz currently serves on the Board of Directors of the Financial Therapy Association. In this interview the editors of the Journal of Financial Therapy ask questions related to what drives Dr. Klontz as a consultant/therapist.
Keywords: Klontz; marriage and family therapy; psychology